An exploration of green practices categories, challenges and future demand in Malaysia hotels / Muhammad Fauzi Mokhtar - Mokhtar, Muhammad Fauzi (2024)
Malaysia attracts millions of tourists each year, bringing in billions of dollars in tourism revenue. In 2021, there were 5,213 hotels to accommodate the growing number of tourists, making hotels a major contributor to the tourism income. However, this influx of hotels poses a threat to the environment due to the large amount of waste they generate. While many people support the idea of sustainable or green hotels to protect the environment, these eco-friendly practices are not widely adopted in the lodging industry. This research aimed to identify the green practices categories, challenges, and future needs of green hotels in Malaysia. A model outlining practical green hotel practices was proposed, and interviews were conducted with hotel owners, managers, employees, and tourists to gain insights. The research proposed four categories of green practices: cost-saving initiatives, nature-friendly initiatives, technology-driven initiatives, and other innovative measures. Common challenges faced by hoteliers included high costs, government regulations and certification requirements, and limited access to technology and expertise. Additionally, all surveyed tourists expressed interest in staying at green hotels, indicating a potential future demand for eco-friendly accommodations. Factors influencing this interest included a pro-environmental attitude among tourists. The proposed model for successful Malaysian green hotels should prioritize both technology and environmentally friendly practices. This research helps hoteliers to understand the challenges they face for better allocation of their resources. It also provides valuable insights for government agencies to develop policies that encourage green hotel practices and promote them to tourists. Additionally, this study offers a foundation for future research on green hotels.